3-D printed variable phase shifter - Gillatt,BTW; D'Auria,M; Otter,WJ; Ridler,NM; Lucyszyn,S (IEEE Microwave and Wireless Component Letters, 2016)
This letter presents the first fully 3-D printed microwave variable phase shifter. The design methodology for a 3-D printable dielectric flap metal-pipe rectangular waveguide variable phase shifter is described. The ABS building material was independently characterized, revealing a dielectric constant of 2.34 and loss tangent of only 0.0015 at 10 GHz. The predicted and measured performance is given, demonstrating a maximum relative phase shift of 142 degrees at 10 GHz, with a near uniform relative phase shift across the whole of X-band and a low variation in differential-phase group delay.